Similar Neural Correlates of Planning and Execution to Inhibit Continuing Actions - Omata, Kei; Ito, Shigeru; Takata, Youhei; Ouchi, Yasuomi (Frontiers in Neuroscience, 2018)
Inhibition of action is involved in stopping a movement, as well as terminating unnecessary movement during performance of a behavior. The inhibition of single actions, known as response inhibition, (Inhibition of the urge to respond before or after actions) has been widely investigated using the go/no-go task and stop signal task. However, few studies focused on phase and volition-related inhibition after an action has been initiated. Here, we used functional magnetic resonance imaging (fMRI) to investigate the neural correlates of planning and execution underlying the voluntary inhibition of ongoing action. We collected fMRI data while participants performed a continuous finger-tapping task involving voluntary and involuntary (externally directed) inhibition, and during the initiation of movement. The results revealed areas of significantly greater activation during the preparation of inhibition of an ongoing action during voluntary inhibition, compared with involuntary inhibition, in the supplementary (SMA) and pre-supplementary motor areas, dorsolateral prefrontal cortex, inferior frontal gyrus (IFG), inferior parietal lobe, bilateral globus pallidus/putamen, bilateral insula and premotor cortex. Focusing on the period of execution of inhibition of ongoing actions, an event-related fMRI analysis revealed significant activation in the SMA, middle cingulate cortex, bilateral insula, right IFG and inferior parietal cortex. Additional comparative analyses suggested that brain activation while participants were planning to inhibit an ongoing action was similar to that during planning to start an action, indicating that the same neural substrates of motor planning may be recruited even when an action is ongoing. The present finding that brain activation associated with inhibiting ongoing actions was compatible with that seen in response inhibition (urge to stop before/after actions) suggests that common inhibitory mechanisms for motor movement are involved in both actual and planned motor action, which may be beneficial to keep behavior resiliently.